Dietary Effect of Withania somnifera Root Powder on Growth, Hematobiochemical Parameters, Immunity, and Disease Resistance to Aeromonas hydrophila in Cyprinus carpio - Syed Sikandar Habib; Muhammad Qamar Saeed; Samrah Masud; Osman Sabri Kesbiç; Javed Ahmed Ujan; Cristina Cravana; Salim S. Al-Rejaie; Mohamed Mohany; Francesco Fazio (Aquaculture Nutrition)
This study investigates the influence of Withania somnifera root powder (WSRP) on different aspects of common carp (Cyprinus carpio), including growth, hematobiochemical parameters, antioxidant status, nonspecific immune response, and resilience to bacterial infections. Over a 60-day period, 180 common carp fingerlings (11.73 ± 0.52 g) were subjected to diets supplemented with increasing WSRP levels (0 (control), 1% (WSRP1), 2.5% (WSRP2.5), and 4% (WSRP4)). Nonspecific immune parameters were evaluated using serum samples collected at intervals of 0, 20, 40, and 60 days. After the feeding trial, the fish underwent experimental challenge with Aeromonas hydrophila, and relative percentage survival (RPS) was monitored for 14 days. The findings revealed a considerable (p <0.05) enhancement in growth performance and a decreased feed conversion ratio (FCR) with increasing WSRP supplementation. Additionally, hematological and biochemical profiles exhibited improvements in groups receiving WSRP-enriched diets. Fish serum antioxidant status showed a significant (p <0.05) increase, as indicated by increased activities of total antioxidant capacity (TAC), superoxide dismutase (SOD), catalase (CAT), and reduced glutathione (GSH) in WSRP4. WSRP-supplemented diets led to remarkable enhancements in lysozyme activity (p=0.001), phagocytic activity (p=0.002), and RPS (p=0.003), peaking in WSRP4 at day 60. Furthermore, WSRP2.5 and WSRP4 demonstrated a substantial decrease (p >0.05) in serum glucose and cortisol levels compared to other groups. In conclusion, WSRP proves valuable for enhancing growth, blood parameters, antioxidant balance, immune response, and infection resistance in common carp, especially at 2.5%–4% dietary supplementation levels. In the future, it will be crucial to study the long-term effects of WSRP supplementation on fish health, as well as its potential for large-scale aquaculture and economic viability in the aquafeed industry.